FUNCTIONAL STATE OF LEFT VENTRICULAR IN DIFFERENT METHODS OF RESTORATION OF CORONARY BLOOD FLOW IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH COMPLICATED ACUTE INSUFFICIENCY WITH INSUFFICIENCY - A. K. Koyirov; S. R. Kenjaev; S. SH. Khaitov; U. SH. Ganiev; M. S. Mirmaksudov (Евразийский Кардиологический Журнал, 2019)
Over the past decade it has increased the share of endovascular treatment of coronary heart disease (CHD) in the world. The choice of this treatment strategy of CHD, to counterbalance the surgical treatment in combination with conservative therapy caused the immediate efficacy and safety of the endovascular procedure to achieve adequate restoration of coronary blood flow in the majority of cases. Primary endovascular restoration of coronary blood flow has several advantages over thrombolytic therapy. There is evidence that reperfusion of the myocardium using the endovascular procedure is more than 95 % of patients with acute ST-segment elevation myocardial infarction (STEMI), then thrombolytic therapy restoration of blood flow is achieved only 7075 %. Endovascular method promotes effective limitation of the size of the damaged myocardium in the early stages of the onset of the disease, prevents the development of residual stenosis in the infarct-related artery (IRA) and pathological remodeling of the left ventricle (LV) and as a result, leads to a reduction not only in-hospital mortality, but and improved survival of patients in distant periods. After the restoration of blood flow in some way in the area of the IRA is a change in contractility parameters, the geometry of the myocardium and central hemodynamics in general, which in turn determine the future course of the disease and the tactics of treatment. Today, in connection with the development and widespread use of modern methods of restoring coronary blood flow in AMIST, great attention is paid to the prevention of early pathological LV remodeling, which allows to influence the prognosis and survival of patients. Introduction (goals/objectives): The goal of the study is to compare the indices of contractility and diastolic myocardial dysfunction in patients with acute myocardial infarction complicated by acute cardiac failure after endovascular intervention and thrombolytic therapy.